1999
DOI: 10.1212/wnl.53.8.1825
|View full text |Cite
|
Sign up to set email alerts
|

APOE-ε4 is associated with less frontal and more medial temporal lobe atrophy in AD

Abstract: We found smaller volumes in the temporal lobe regions but larger volumes in the frontal lobes with increasing APOE-e4 gene dose in AD patients. These data suggest a region-specific biological effect of the e4 allele in the brains of AD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
98
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 44 publications
9
98
2
Order By: Relevance
“…In contrast, another recent study surveying the whole brain using voxel-based morphometry identified relatively more prominent MTL atrophy in carriers but did not find areas where gray matter volume was greater in ε4 carriers than noncarriers (35). Finally, two older studies of select regions reported evidence of smaller frontal lobe volumes in noncarriers relative to carriers (19,21), but again with no psychometric differences, likely owing to small sample size.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…In contrast, another recent study surveying the whole brain using voxel-based morphometry identified relatively more prominent MTL atrophy in carriers but did not find areas where gray matter volume was greater in ε4 carriers than noncarriers (35). Finally, two older studies of select regions reported evidence of smaller frontal lobe volumes in noncarriers relative to carriers (19,21), but again with no psychometric differences, likely owing to small sample size.…”
Section: Resultsmentioning
confidence: 73%
“…Conflicting results have also been reported from the limited investigations of cortical anatomy, with some studies reporting no difference and others reporting more robust regional atrophy in ε4 carriers (20,23). Finally, there are a few reports of greater atrophy in noncarriers either in select regions, such as the frontal lobe, or in global measures of brain volume (17,(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Step 2 Step 3 why effects on global hippocampal volume are subtler, observed in some studies [4][5][6][7][8][9] but not others. [10][11][12] A particular strength of our study is the finding of a possible symptomatic consequence of APOE e4-associated CA1-SRLM thinning, which appeared to mediate the relationship between carrier status and the integrity of episodic memory.…”
Section: Resultsmentioning
confidence: 99%
“…Structural imaging studies of AD patients have revealed morphological deficits in carriers of the ApoE4 allele versus noncarriers (Lehtovirta et al, 1995;Juottonen et al, 1998;Geroldi et al, 1999;Mori et al, 2002). In healthy elderly subjects, the ApoE4 allele is associated with diminished CNS glucose utilization (Reiman et al, 2004) and some studies have reported impairment in cognitive function (Deary et al, 2002).…”
Section: Introductionmentioning
confidence: 99%